Linkage integrated fin ray gripper capable of safe adaptive grasping for tomato harvesting - An, Byeongchan; Choi, Taeyong; Kim, Uikyum (Computers and Electronics in Agriculture, 2025)
Fruit harvesting is a labor-intensive process. However, the number of people working in the agricultural sector is steadily decreasing. To address this issue, the development of a fruit harvesting robot is essential. In this study, a novel gripper was developed to preserve the quality of harvested tomatoes by cutting the stems while providing soft adaptive grasping. The gripper was designed by combining a fin ray and linkage mechanism. The fin ray exhibits a soft adaptive behavior for safe grasping, which adaptively operates the linkage to cut the stem. To prevent damage to tomatoes, we propose a design method based on a pseudo-rigid body model to effectively distribute the grasping force of the fin ray. The linkage was designed considering the torque and rotation angle of the links. The fin ray design method was verified through experiments that compared the force distribution effectiveness of the optimized fin ray with that of other fin rays. A maximum cutting force of 13.9 N was measured in the experiments. The harvesting experiments conducted in a laboratory environment with real tomatoes demonstrated that the developed gripper was capable of harvesting tomatoes up to 73 mm in size.
Keywords: Adaptive tomato harvesting; Agricultural sector; Design method; Fin ray optimization; Fruit harvesting; Labor intensive process; Linkage integrated fin ray; Number of peoples; Ray optimizations; Soft grasping; Adaptive tomato harvesting; Fin ray optimization; Linkage integrated fin ray; Soft grasping